2015
DOI: 10.1016/j.jamda.2014.11.007
|View full text |Cite
|
Sign up to set email alerts
|

Evaluations of Home Care Interventions for Frail Older Persons Using the interRAI Home Care Instrument: A Systematic Review of the Literature

Abstract: This systematic review can help researchers to plan evaluation of interventions in home care. The interRAI HC instrument proves to be a comprehensive tool to measure outcomes and can serve as an evaluation instrument for interventions. It can also be used as an intervention itself, when caregivers use the tool and its outcome measures to implement a care plan.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
30
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 40 publications
(32 citation statements)
references
References 36 publications
0
30
0
Order By: Relevance
“…Set against these limitations, the interRAI offers many promising opportunities for regional, national and international comparative studies using the same standardised measures 5,9,18 . Moreover, within NZ, through the matching with NHI numbers, an enhanced range of medium‐term health outcomes (such as hospital visits, admission and re‐admissions, need for residential care, morbidity and mortality) can be investigated.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Set against these limitations, the interRAI offers many promising opportunities for regional, national and international comparative studies using the same standardised measures 5,9,18 . Moreover, within NZ, through the matching with NHI numbers, an enhanced range of medium‐term health outcomes (such as hospital visits, admission and re‐admissions, need for residential care, morbidity and mortality) can be investigated.…”
Section: Discussionmentioning
confidence: 99%
“…While the information gained is used primarily to inform person‐level decisions around care, opportunities exist to better understand older persons’ health and their health care needs within their own home setting. Internationally, there are numerous activities and population studies using the interRAI, 17–20 but, as yet, relatively little has been published in NZ. Critical to these investigations is an understanding of the interRAI‐HC population and the quality of the recorded data.…”
mentioning
confidence: 99%
“…All adult instruments are built on a minimum set common set of common items, as well as specialised items relevant to particular contexts and patient groups, and are designed to track persons longitudinally over time and across multiple care settings. These instruments have been continuously improved and validated against other commonly used instruments for use in long-term care, acute and post-acute care, home care, mental health, palliative and community settings [16][17][18][19][20][21][22][23][24][25]. The item domains of these instruments have been shown to have good inter-rater reliability [16] and have been adopted internationally, including countries in North America, Europe, the Middle East, Australasia and East and South East Asia [26,27].…”
Section: Introductionmentioning
confidence: 99%
“…The interRAI home care (interRAI-HC) is probably the most well-researched and supported community-based multi-domain assessment globally [6]. Two recent systematic reviews of the interRAI Home Care instrument have shown that it can be supportive tool for quality care planning to identify problems and risk situations and can foster collaboration between healthcare professionals within and across care settings and improve communication between caregivers [17,24]. Together with case management, it has been shown to reduce hospital admissions, length of stay, and thus, reduce additional expenditure and associated costs [5,17,24] The Check-Up instrument was speci cally designed to address the needs and status of older persons living in the community including those receiving primary care services to inform individual care planning.…”
Section: Introductionmentioning
confidence: 99%
“…Loneliness is also related to negative health outcomes such as poor health or illness , cognitive impairment , psychological distress , depression and anxiety . Older adults receiving home care are one vulnerable group especially exposed to several risk factors . Loneliness and the meaning of loneliness among older adults living at home but in need of home care are examined in this study.…”
Section: Introductionmentioning
confidence: 99%